2013
DOI: 10.1177/0003319713504819
|View full text |Cite
|
Sign up to set email alerts
|

Combined Coronary Artery Bypass Grafting and Open Abdominal Aortic Aneurysm Repair Is a Reasonable Treatment Approach

Abstract: We reviewed the literature for studies investigating the outcomes of combined 1-stage coronary artery bypass grafting (CABG) and abdominal aortic aneurysm (AAA) open repair (OR) procedures. An electronic search of the English literature was conducted using the PubMed, EMBASE, and Cochrane databases. Age, coronary heart disease severity, AAA size, mean duration from CABG to AAA OR procedures, details of each procedure, mortality, and morbidity rates were analyzed. Between 1994 and 2012, 12 studies (256 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In fact, although endovascular AAA repair is preferred over open repair procedures, a combined 1-stage coronary artery bypass grafting and AAA open repair procedures can be performed with acceptable mortality and morbidity. 22 Asymptomatic CeVD in Patients With AAA…”
Section: Discussionmentioning
confidence: 99%
“…In fact, although endovascular AAA repair is preferred over open repair procedures, a combined 1-stage coronary artery bypass grafting and AAA open repair procedures can be performed with acceptable mortality and morbidity. 22 Asymptomatic CeVD in Patients With AAA…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 , 2 ] The prevalence of CAD in patients with AAA has been estimated to be as high as 50%. [ 3 ] The risks of perioperative mortality, myocardial ischemia, and adverse long-term outcomes are significantly increased in patients undergoing AAA repair with comorbid CAD. [ 4 ] In patients with severe CAD and peripheral vascular disease, the usual treatment is first myocardial revascularization or percutaneous coronary intervention followed by AAA repair (staging surgery).…”
Section: Discussionmentioning
confidence: 99%
“…4 It was reported that combined CABG and AAA repair had a 30-day mortality of approximately 7.8%. 31 PCI with EVAR was considered a less-invasive procedure that could have a lower mortality. 9 The rupture risk of aneurysms increased with increasing of aneurysm diameter.…”
Section: Discussionmentioning
confidence: 99%